Escape room [videorecording (DVD)] - Robitel, Adam, 1978-; Russell, Taylor, 1994-; Miller, Logan, 1992-; Woll, Deborah Ann, 1985- (Sony Pictures Home Entertainment, 2019)
When a group of strangers are given black boxes with tickets to an escape room with a chance to win money, they discover that the room has more extreme conditions than expected, and must fight for survival.